2020
DOI: 10.1021/acsami.0c01001
|View full text |Cite
|
Sign up to set email alerts
|

Realizing 22.3% EQE and 7-Fold Lifetime Enhancement in QLEDs via Blending Polymer TFB and Cross-Linkable Small Molecules for a Solvent-Resistant Hole Transport Layer

Abstract: Poly[(9,))] (TFB) has been widely used as a hole transport layer (HTL) material in cadmium-based quantum dot lightemitting diodes (QLEDs) because of its high hole mobility. However, as the highest occupied molecular orbital (HOMO) energy level of TFB is −5.4 eV, the hole injection from TFB to the quantum dot (QD) layer is higher than 1.5 eV. Such a high oxidation potential at the QD/HTL interface may seriously degrade the device lifetime. In addition, TFB is not resistant to most solvents, which limits its app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
75
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 60 publications
0
75
1
Order By: Relevance
“…After adding TFB HTL, the injection loss of holes should be reduced. Besides, the carrier mobility of TFB is 1 x 10 -3 cm 2 /(v • s) [11] , which is more favorable for hole transport compared with PVK (2.5 x 10 -6 cm 2 /(v • s)) [12] and Poly-TPD (1 x 10 -4 cm 2 /(v • s)) [13] . The LUMO energy level of TFB is -2.3eV, which could effectively block electron from entering HTL, thus avoiding recombination light emission in the TFB layer and effectively confining electron in perovskite layer.…”
Section: Methodsmentioning
confidence: 99%
“…After adding TFB HTL, the injection loss of holes should be reduced. Besides, the carrier mobility of TFB is 1 x 10 -3 cm 2 /(v • s) [11] , which is more favorable for hole transport compared with PVK (2.5 x 10 -6 cm 2 /(v • s)) [12] and Poly-TPD (1 x 10 -4 cm 2 /(v • s)) [13] . The LUMO energy level of TFB is -2.3eV, which could effectively block electron from entering HTL, thus avoiding recombination light emission in the TFB layer and effectively confining electron in perovskite layer.…”
Section: Methodsmentioning
confidence: 99%
“…Especially, CdSe‐ and lead chalcogenide‐based QDs are generally the material of choice for visible‐ and IR‐emitting QLEDs, respectively. [ 53,137–147 ] For example, to take advantage of superior properties of QDs, a number of high‐performance CdSe‐based QLEDs were investigated by optimizing the specific core/shell structures and ligand engineering and using valid charge carrier transport and blocking interlayers. In 2014, Dai et al reported CdSe–CdS core–shell QD‐based red LED with solution‐processed inorganic emissive layer, insulating layer between QDs, and oxide electron‐transport interlayers, resulting in the high external quantum efficiencies (EQEs) of up to 20.5%, a low efficiency roll‐off up to 15.1%, and a long operational lifetime of more than 100 000 h at 100 cd m −2 .…”
Section: Qd‐based Photonic Devicesmentioning
confidence: 99%
“…[ 138 ] By adapting well‐designed QDs and precisely controlled synthesis methods with novel structures, which have matched with balanced carrier transport interlayers, recent state‐of‐the‐art QLEDs have made a breakthrough in their photonic performance such as the peak EQEs of up to 21% in the visible wavelength region. [ 139,140,145 ] More recently, Song et al reported alloyed Zn 1– x Cd x Se QD‐based red LED showing the peak EQEs of up to 30.9%, a low efficiency roll‐off up to 25%, and a long operational lifetime of more than 1 800 000 h at 100 cd m −2 ( Figure a–c). [ 141 ] The use of precisely controlled shell growth with an intermediate ZnSe and outer ZnS layer combination and suitable surface ligand modification with 2‐ethylhexane‐1‐thiol improved hole transport efficiency and resulted in more balanced charge injection.…”
Section: Qd‐based Photonic Devicesmentioning
confidence: 99%
“…So far, various QD patterning methods have been proposed, such as electro‐hydrodynamic jet printing, [ 11–14 ] transfer printing, [ 15–17 ] and inkjet printing. [ 18–26 ] Among these techniques, inkjet printing is highly advantageous for the implementation of full‐color QLED displays because of its fast processing time, comparatively straightforward quality that causes a minimal material usage by the drop‐on‐demand (DOD) process with high precision and accuracy, [ 18 ] and ability to be used in large‐area displays because it does not require an individual fine metal mask for RGB colors. Despite these advantages, the performance of inkjet‐printed devices is generally lower than that of spin‐coated devices.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a number of researches focus on finding ways to improve the uniformity of inkjet‐printed films. [ 18–26 ] Moreover, the depositing morphologies of the inkjet droplets affect the efficiency, stability, and performance of the inkjet‐printed devices. In order to control this phenomenon, a widely used method in controlling the drying conditions of a droplet is employed using cosolvents, [ 11,19–26 ] mixing surfactants, [ 27–29 ] and/or fine‐tuning viscosity, [ 30–32 ] which optimized the Marangoni flow and capillary flow.…”
Section: Introductionmentioning
confidence: 99%